2014
DOI: 10.1093/brain/awu058
|View full text |Cite
|
Sign up to set email alerts
|

The subthalamic nucleus and inhibitory control: impact of subthalamotomy in Parkinson’s disease

Abstract: The subthalamic nucleus (STN) is hypothesized to play a central role in the rapid stopping of movement in reaction to a stop signal. Single-unit recording evidence for such a role is sparse, however, and it remains uncertain how that role relates to the disparate functions described for anatomic subdivisions of the STN. Here we address that gap in knowledge using non-human primates and a task that distinguishes reactive and proactive action inhibition, switching and skeletomotor functions. We found that specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 41 publications
9
72
0
1
Order By: Relevance
“…PD is characterized by over-synchrony between basal ganglia and cortex (Brown, 2003; George et al, 2013; Swann et al, 2015); and it is thought that this ‘locking’ prevents cortico-basal-ganglia circuits from operating properly. Indeed, multiple studies show PD patients off treatment are impaired at stopping (George et al, 2013; Obeso et al, 2014; Obeso et al, 2011; Swann et al, 2011). We hypothesize that the mental inflexibility in PD is at least partly explained by a system that is not properly interruptible by new information (because the STN-mediated interrupt is ineffective due to oversynchrony).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD is characterized by over-synchrony between basal ganglia and cortex (Brown, 2003; George et al, 2013; Swann et al, 2015); and it is thought that this ‘locking’ prevents cortico-basal-ganglia circuits from operating properly. Indeed, multiple studies show PD patients off treatment are impaired at stopping (George et al, 2013; Obeso et al, 2014; Obeso et al, 2011; Swann et al, 2011). We hypothesize that the mental inflexibility in PD is at least partly explained by a system that is not properly interruptible by new information (because the STN-mediated interrupt is ineffective due to oversynchrony).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is converging evidence for the role of the STN from several other methods. Clinically-induced lesions to the STN in patients (subthalomotomies) affected stopping (Obeso et al, 2014) and several studies have shown the impact of STN deep brain stimulation (DBS) on stopping. Three of these studies found a speeding of stopping (i.e., SSRT) when stimulation was bilateral (Mirabella et al, 2011; Swann et al, 2011; van den Wildenberg et al, 2006) while one did not (Obeso et al, 2013).…”
Section: The Brain’s Network For Global Motor Stoppingmentioning
confidence: 99%
“…Several studies have suggested that the right subthalamic nucleus and right inferior frontal gyrus are correlated with response inhibition, suggesting that they form a frontal-subcortical pathway of control inhibition (40, 45, 46). The right-lateralized subthalamic nucleus and inferior frontal gyrus have been used as regions of interest for response inhibition tasks (i.e., the stop signal task and go/no-go task) in studies reporting compromised impulse control in alcohol-dependent individuals (37, 38) and reduced ability to cancel prepotent responses (47), as well as in lesion studies (48), deep brain stimulation studies (49), and fMRI studies (50) of response inhibition in individuals with Parkinson's disease. Studies of in vivo deep brain stimulation of the sub-thalamic nucleus in Parkinson's patients (51) and in animal models (52) have shown a decrease in craving and regulation of substance preference, indicating the involvement of this brain region in neural processes that underlie addictive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Verbal fluency may be particularly vulnerable to dis-393 ruption, as deficits are often seen in PD and become 394 increasingly common in later stages of the illness [16]. trol, reward learning, and risk decision-making [18].…”
mentioning
confidence: 99%